Determinants of Company Value: Empirical Evidence from Consumer Goods Industrial Companies in Indonesia - Purnama, Maria Goreti; Yuniarti, Sari; Terdpaopong, Kanitsorn; Subiyantoro, Edi; Khouroh, Umu (Jurnal Manajemen Bisnis, 2024)
Research Aims: Investors focus on a company's value before investing, which can benefit shareholders. This study, thus, investigates how factors like liquidity, debt, profits, growth, and investment opportunities affect a company's value, with dividend policy playing a role.Design/Methodology/Approach: This study examined companies in the consumer goods industry listed on the IDX from 2018 to 2021. The authors collected data from 71 selected companies using purposive sampling. The analysis method employed was Moderating Regression Analysis (MRA).Research Findings: The findings demonstrated that Debt to Asset Ratio (DAR), Return on Assets (ROA), and Investment Opportunity Set (IOS) strongly affected Price to Book Value (PBV) positively. However, Current Ratio (CR) and Growth did not significantly affect PBV. Additionally, the Dividend Payout Ratio (DPR) did not influence the relationship between CR, DAR, and Growth with PBV. Also, it did moderate the relationship between ROA and IOS with PBV.Theoretical Contribution/Originality: The research findings contribute to our understanding of the factors that impact the market value of companies in the consumer goods industry listed on the IDX.Practitioners/Policy Implications: It is crucial to examine specific variables that have a significant impact on PBV, while other variables may not play a vital role. This can help practitioners, academics, and investors make more informed decisions based on in-depth analysis of company performance and value.Research Limitations/Implications: The limitations include limited panel data, a single industry focus, the absence of supportive data on individual company investment variations, and no consideration of industry risk, market policies, or investor preferences.